Identifying the Dimensions of the Design-Oriented Approach to Organizational Change Acceptance in Tehran Bus Company - KEIMASI, MASOUD; ANSARI, MANOUCHEHR; CHEHRAZI, SAMAN (The journal of contemporary issues in business and government, 2021)
Organizational change does not take place without introduction. The drivers of change usually derive from the organizational environment or market. These drivers include things like competitors' bold moves, new technology with changing government regulations, and manager's inefficiency can be a driver for change in the organization. The purpose of this study is to identify the dimensions of the design-oriented approach to organizational change in Tehran Bus Company. The statistical population of the study is the experts of Tehran Bus Company. The data collection tool was an interview that identified the dimensions of the model using the view of 20experts and the grounded approach. Interviews have been coded using MAXQDA software. The results of open coding of qualitative data collected using interview tool showed that 141 open codes out of 374 concepts were identified. 23 main categories and 24 subcategories are categorized. The central category in this research is the acceptance of organizational change. Causal conditions based on the trust-building of experience of previous changes, environmental requirements, organizational requirements, motivational system, about leaders to strategic change management, selection and appointment of managers and employees, investment in human resources, public relations, organizational communication, monitoring and feedback, executive performance of manager, about background conditions, considerations related to infrastructure and financial resources, considerations related to organizational culture, considerations related to organizational structure, considerations related to organizational climate, intervention conditions, on the support of stakeholders and people outside the organization, characteristics of managers, characteristics of human resources, networking, outcomes and results, on the promotion of social capital, satisfaction resulting from change, has been mentioned.